Invited review: Ruminal acidosis and its definition—A critical review - H.M. Golder; I.J. Lean (Journal of Dairy Science)
ABSTRACT: Ruminal acidosis occurs as a continuum of disorders, stemming from ruminal dysbiosis and disorders of metabolism, of varying severity. The condition has a marked temporal dynamic expression, resulting in cases expressing quite different rumen concentrations of VFA, lactic acid, ammonia, and rumen pH over time. Clinical ruminal acidosis is an important condition of cattle and subclinical ruminal acidosis (SRA) is very prevalent in many dairy populations, with estimates between 10% and 26% of cows in early lactation. Estimates of the duration of a case suggest that the lactational incidence of the condition may be as high as 500 cases per 100 cows in the first 100 d of lactation. Historical confusion about the etiology and pathogenesis of ruminal acidosis led to definitions that are not fit for purpose, as acidic ruminal conditions solely characterized by ruminal pH determination at a single point fail to reflect the complexity of the condition. Use of a model based on integrated ruminal measures, including VFA, ammonia, lactic acid, and pH, for evaluating ruminal acidosis is fit for purpose, as indicated by meeting postulates for assessing metabolic disease, but requires a method to simplify application in the field. Although it is likely that this model, which we have termed the Bramley acidosis model (BAM), will be refined, the critical value in the model is that it demonstrates that ruminal acidosis is much more than ruminal pH. Disease, milk yield, and milk composition are more associated with the BAM than rumen pH alone. Two single VFA, propionate and valerate, are sensitive and specific for SRA, especially when compared with rumen pH. Even with the use of such a model, astute evaluations of the condition, whether in experimental or field circumstances, will be aided by ancillary measures that can be used in parallel or in series to enhance diagnosis and interpretation. Sensing methods, including rumination detection, behavior, milk analysis, and passive analysis of rumen function, have the potential to improve the detection of SRA; however, these may advance more rapidly if SRA is defined more broadly than by ruminal pH alone.